Derivative ultraviolet spectrophotometric method to determinate synephrine in lipid nanocarrier - Baldissera, Denise Bom; Ziegler, Sabrina; Steffler, Mírian Carine Ribeiro; Raffin, Renata Platcheck; Roggia, Isabel; Dalcin, Ana Júlia Figueiró; Gomes, Patrícia (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
Gynoid lipodystrophy (GLD) is a common dermatological condition that affects especially women after the puberty. GLD is concentrated mainly in the pelvic region, lower limbs, and abdomen. Several therapies for physical and mechanical methods are used for the treatment of GLD. However, cosmetics products are distinguished by ease of access and practicality of application. The nanotechnology has contributed to improving the performance of cosmetics and consumer acceptance, providing an alternative for increasing the stability, controlled liberation and, mainly, obtaining of products more aesthetically pleasing. The objective this work was the development and validation of a method by the spectrophotometry ultraviolet derived for determination of synephrine (SFN) specifically in a lipid carrier containing dihydromyricetin, diosgenin, and synephrine. The method showed selectivity for SFN at 239 nm in the presence of other active compounds using second order derivative, Δλ 10.000 and scale factor 50. The parameters, such as linearity, precision, accuracy and robustness were analyzed during its development. The results were analyzed statistically using the GraphPad Prism software version 5.0. The standard curve showed a correlation coefficient of 0.9983. The precision showed good repeatability (RSD = 2.13) and intermediate precision (RSD = 1.93). The accuracy of the method was confirmed by the mean recoveries of 100.79%. The robustness was evaluated by small changes in the conditions of sample analysis, and it was observed that using of ethanol grade per analysis was essential for this analysis. Thus, the developed and validated methodology demonstrated to be specific, linear, accurate, precise and robust. Furthermore, its execution is quick and straightforward, offering an alternative less expensive for determination of SFN in lipid nanocarrier.